Gingivitis and Oral Health Practices among Pregnant Women - Sonia, Zinat Ara; Siddiqua, Fahmida (Journal of Dentistry and Allied Science, 2025)
Purpose: Gingivitis is a more familiar oral health issue among pregnant women, mainly due to the hormonal rush and increased susceptibility to plaque-induced inflammation. The study aimed to assess the prevalence of gingivitis and evaluate oral health practices among pregnant women. Methods: A descriptive type of cross-sectional study was conducted on 206 pregnant women in OPD, Gynae and Obs, Mugda Medical College Hospital and Maternal & Child Health Training Institute, Azimpour, Dhaka from 1st January to 31st December 2022. In order to collect data, a face-to-face interview was conducted by using a pretested semi-structured questionnaire. Clinical examination was carried out in daylight and the descriptive statistics included the frequencies, percentages, mean, median and standard deviation of the findings, while the inferential statistics included a chi-square test to find out the association between socio-demographic, oral health practices and dental visits of pregnant women with gingivitis. Results: An association between socio-demographic factors with oral health factors showed statistically not significant (P) value but association between pregnancy trimester with bleeding gum, swollen gum, painful gum and reddish gum of participants. Chi-square test shows the association is statistically significant (P0.05) and value are (0.000, 0.015, 0.031 & 0.001). Another association between oral hygiene practice and dental visit factor showed a non-significant P-value. Conclusion: Step-wise approaches are required during each trimester of pregnancy and dental check-ups should be incorporated into antenatal check-ups. Journal of Dentistry and Allied Science, Vol. 8 No 2: 34-47